A granular energy-controlled boundary condition for discrete element simulations of granular flows on erodible surfaces. (February 2023) - Zhu, Chongqiang; Huang, Yu; Sun, Jin
Abstract: Entrainment of the substrate, which can cause the volume of geophysical flows to increase by many times and greatly affects its mobility, occurs frequently. Even though many large-scale studies have been conducted to investigate entrainment during flows, particle-scale studies are urgently needed to understand this complex process. We propose a novel configuration with an energy-controlled boundary to model inclined granular flows on erodible surfaces with the aim of investigating the rheological features of granular flows with entrainment. The erosion degree is controlled by adjusting the energy of the bottom granular bed. The bulk velocity, stress, microstructure, and constitutive behavior are systematically analyzed. Our simulations capture the exponentially decaying velocity in the creeping region, confirming that this configuration can be applied to study geophysical flows with entrainment. The velocity at the free surface increases with erosion depth, which means entrainment can greatly enhance the mobility of granular flow. However, the flow in the shear band still belongs to the inertial regime. The novel energy-controlled configuration provides effective and efficient way to investigate granular flows on erodible surfaces, serving as an initial step to understand geophysical flows involving entrainment, which is essential to develop new geo-disaster mitigation strategy.